Acute injuries in American collegiate taekwondo competitions: a prospective study spanning four competitive seasons - Zhao, R. T.; Medina, G.; Chen, E. T.; Oh, L. S. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Injury patterns are well-documented for taekwondo competitions prior to the use of an electronic chest protector for scoring tabulation. To see if injury rates and types changed following this rule change that transformed the fighting style in taekwondo, we investigated injuries in collegiate taekwondo competitions in the USA. METHODS: Data were collected at eight collegiate taekwondo tournaments from April 2018 to December 2019. All injured athletes seen at the first-aid station were invited to complete a survey that included injury location, type, and mechanism of injury. Injury rates were calculated per 1000 athlete-exposures (A-Es) and minute-exposures (M-Es). Risk factors were modeled using logistic regression and Chi2 analysis. RESULTS: Out of 1096 athletes, 194 athletes reported 275 acute injuries. We found an injury risk of 17.7/100 athletes (95% CI: 15.4, 20.0) and injury rate of 68.9/1000 A-E (95% CI: 60.7, 77.0) which was comparable to previous studies. The most common injuries were contusions to the lower limbs. In contrast to prior reports, men were injured more frequently from delivering a kick and women from receiving a kick. Populations at higher risk for injury included those with low belt rank and middle weight class for women. CONCLUSIONS: It appears that the new fighting style did not affect injury rates. Injury locations and types remain similar, but the mechanisms of injury have reversed as men are more injured from attacking and women from defending. There remains a strong need for research to improve protective equipment and safety rules in taekwondo.